Is Corona Virus an Extraordinary Biological Weapon? (Indonesian Media Perspective in the Early COVID-19 Pandemic)) - Arina Haque; Iffat Maimunah; Wildana Wargadinata (Universitas Pendidikan Ganesha, 2022)
The coronavirus phenomenon at the beginning of 2020 provoked many conspiracy theories from experts in various scientific fields. One opinion supported by many related facts is the suspicion of the coronavirus or COVID-19 as a biological weapon of mass destruction. This research aims to review and describe the phenomenon of the coronavirus, which is considered a biological weapon of mass destruction, based on the facts circulating in various media in Indonesia during the early days of the COVID-19 pandemic. This type of research is descriptive qualitative with a framing analysis approach based on the perspective of Erving Goffman. The source of data in this research is credible news about the coronavirus. The results of the research have found that five facts support the alleged coronavirus as a biological weapon of mass destruction, which consists of (1) Recognition of indications that the coronavirus is an artificial virus; (2) The fact that the coronavirus is a threat; (3) Not all countries in the world comply with UN multilateral treaties on weapons of mass destruction; (4) A statement that the coronavirus was intentionally produced in a laboratory; and (5) The existence of United States interests. As for the refutation of the allegation of the coronavirus phenomenon as a mass murderer, the results of this research indicate that there are four corroborating rebuttals, namely: (1) China's denial of the accusation of the maker of the coronavirus; (2) There is no research that proves that the coronavirus is a biological weapon; (3) A statement that there is no intentional element of the Corona Virus outbreak; and (4) There is no evidence of US accusations against China as the maker of the coronavirus.